2005
DOI: 10.1517/14622416.6.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Complex Haplotypic Effects of the ABCB1 Gene on Epilepsy Treatment Response

Abstract: Our results showed that the three loci, C1236T, G2677T and C3435T, jointly influenced the treatment response for epileptic patients. They should be regarded together as a complex polymorphic drug-response system. These findings suggest that examination of the haplotypes of the three loci could be useful in predicting drug resistance in epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
87
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 29 publications
9
87
2
Order By: Relevance
“…Secondly, the definition of outcome has varied between studies, the exception being the Tan et al study, 82 which still failed to replicate the original finding. 81 In particular, Hung et al 86 utilized extreme definitions of drug resistance and drug responsiveness, and this might explain the positive findings of this study. In addition, in this study, there were significant differences in the proportions of patients with temporal lobe epilepsy and epilepsy syndromes between case and control groups, and the association reported may therefore have been with epilepsy aetiology rather than with outcome.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…Secondly, the definition of outcome has varied between studies, the exception being the Tan et al study, 82 which still failed to replicate the original finding. 81 In particular, Hung et al 86 utilized extreme definitions of drug resistance and drug responsiveness, and this might explain the positive findings of this study. In addition, in this study, there were significant differences in the proportions of patients with temporal lobe epilepsy and epilepsy syndromes between case and control groups, and the association reported may therefore have been with epilepsy aetiology rather than with outcome.…”
mentioning
confidence: 62%
“…In fact, only one study made a true effort to correct for multiple testing. 86 By contrast, another study reported up to 300 P-values without any correction. 88 While the rest of the studies did not undertake multiple testing to quite such an extent, even those studies testing for one SNP performed multiple tests through subgroup analysis.…”
Section: Limitations Of Studies Of Therapeutic Drug Response and Recomentioning
confidence: 93%
See 3 more Smart Citations